Elevated diastolic wall shear stress in regurgitant semilunar valvular lesions. Issue 3 (4th February 2019) - Rizk, Judy; Latus, Heiner; Shehu, Nerejda; Mkrtchyan, Naira; Zimmermann, Judith; Martinoff, Stefan; Ewert, Peter; Hennemuth, Anja; Stern, Heiko; Meierhofer, Christian
Abstract : Background: Alterations in wall shear stress (WSS) assessed using 4D flow MRI have been shown to play a role in various vascular pathologies, such as bicuspid aortic valve aortopathy. Most studies have focused on systolic WSS, whereas altered diastolic hemodynamics in regurgitant semilunar valvular lesions have not so far been well characterized. Purpose: To investigate diastolic WSS in aortic and pulmonary regurgitation. Study Type: Retrospective data analysis. Population: Thirty tetralogy of Fallot patients, 19 bicuspid aortic valve patients, 11 healthy volunteers. Field Strength/Sequence: 5 T, 3D time‐resolved phase‐contrast MRI with 3D velocity encoding. Assessment: Estimation of WSS and its axial and circumferential vector components along cardiac cycle timeframes in the proximal main pulmonary artery in pulmonary regurgitation (PR) and in the proximal ascending aorta in aortic regurgitation (AR) as well as in healthy volunteers. Statistical Tests: Wilcoxon matched pairs test was used for intra‐group comparisons and Mann–Whitney test for intergroup comparisons. Correlations were assessed using Spearman correlation. Results: WSS along the entire cardiac cycle was higher in PR and AR in comparison with controls (mean WSS 0.381 ± 0.070 vs. 0.220 ± 0.018, P  < 0.0001; 0.361 ± 0.099 vs. 0.212 ± 0.030, P  < 0.0001; respectively). Peak diastolic WSS was significantly higher than the mean WSS in AR and PR ( P  < 0.0001–0.005). The severity of PR correlated with the peak diastolic axial WSS (Spearman's r s  = 0.454, P  = 0.018), whereas the severity of AR correlated with both peak systolic and diastolic tangential WSS (Spearman's r s  = 0.458, P  = 0.049; r s  = 0.539, P  = 0.017, respectively). Data Conclusion: Elevated diastolic WSS is a component of the altered flow hemodynamics in AR and PR. This may give more insight into the pathophysiologic role of WSS in vascular remodeling in AR and PR. Level of Evidence: 4 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2019;50:763–770.